Geographic Information System (GIS) for ecology: a bibliometric network analysis - Alcaras, Emanuele; Amoroso, Pier Paolo; Figliomeni, Francesco Giuseppe; Parente, Claudio (Ecological Questions, 2024)
Introduced in 1960s to store, analyse, and manipulate data collected for the Canada Land Inventory by mapping information about soils, agriculture, recreation, wildlife, waterfowl, forestry and land use, since their origins Geographic Information Systems (GISs) have had a fundamental role in the study of the environment. As computers systems for capturing, storing, checking, and displaying data related to positions on Earth's surface, GISs have quickly become an effective and powerful tool for addressing ecological issues, analysing the relationship between living things and their habitats, assessing the environmental impact of man-made transformations of a territory. This article aims to show and discuss the results of a study concerning quantitative distribution of GIS for ecology in literature from Scopus database using bibliometric analysis. Bibliometric analysis is a scientific computer assisted review methodology to explore the major research interests in scientific literature, so to identify core research authors, as well as their relationship, by covering articles, conference papers, book chapters and reviews related to a given topic or field. The high number of scientific manuscripts published on the subject (5,204) in the analysed period (1979-2021), remarked the soundness of this topic. While China shows the greatest number of published documents, USA is the country with the most cited documents. Specifically, “remote sensing”, “spatial analysis” and “land use” are the keywords most frequently linked to GIS and ecology, so to underline respectively three aspects: the relevance of environment monitoring by satellite, airplane or drone, the utility of relating ecological questions to the geo-localization, the necessity of produce thematic maps for describing the economic and cultural activities (e.g., agricultural, residential, industrial, and recreational uses) that are practiced at a given place. Since the study shows that trend of publications focusing on the application of GIS for ecology is increasing, further growing is expected in the next future, also considering the ductility that these computer systems provide in different fields.